Effect of warming and grazing on litter mass loss and temperature sensitivity of litter and dung mass loss on the Tibetan plateau - LUO, CAIYUN; XU, GUANGPING; CHAO, ZENGGUO; WANG, SHIPING; LIN, XINGWU; HU, YIGANG; ZHANG, ZHENHUA; DUAN, JICHUANG; CHANG, XIAOFENG; SU, AILING; LI, YINGNIAN; ZHAO, XINQUAN; et al. (Global Change Biology, 2010)
Knowledge about the role of litter and dung decomposition in nutrient cycling and response to climate change and grazing in alpine ecosystems is still rudimentary. We conducted two separate studies to assess the relative role of warming and grazing on litter mass loss and on the temperature sensitivity of litter and dung mass loss. Experiments were conducted for 1-2 years under a controlled warming-grazing system and along an elevation gradient from 3200 to 3800 m. A free-air temperature enhancement system (FATE) using infrared heaters and grazing significantly increased soil temperatures (average 0.5-1.6 °C) from 0 to 40 cm depth, but neither warming nor grazing affected soil moisture except early in the growing seasons at 30 cm soil depth. Heaters caused greater soil warming at night-time compared with daytime, but grazing resulted in greater soil warming during daytime compared with night-time. Annual average values of the soil temperature at 5 cm were 3.2, 2.4 and 0.3 °C at 3200, 3600 and 3800 m, respectively. Neither warming nor grazing caused changes of litter quality for the first year of the controlled warming-grazing experiment. The effects of warming and grazing on litter mass losses were additive, increasing litter mass losses by about 19.3% and 8.3%, respectively, for the 2-year decomposition periods. The temperature sensitivity of litter mass losses was approximately 11% °C⁻¹ based on the controlled warming-grazing experiment. The annual cumulative litter mass loss was approximately 2.5 times that of dung along the elevation gradient. However, the temperature sensitivity (about 18% °C⁻¹) of the dung mass loss was about three times that of the litter mass loss. These results suggest greater warming at night-time compared with daytime may accelerate litter mass loss, and grazing will enhance carbon loss to atmosphere in the region through a decrease of litter biomass and an increase of dung production with an increase of stocking rate in future warmer conditions.